Improving equity and livelihoods in community forestry: a global action research initiative in support of a strategic partnership on rights and resources - Larson, A.M. (Center for International Forestry Research, 2010)
In 2006, the Center for International Forestry Research, in coordination with the Rights and Resources Initiative, launched a global research project in over 30 sites in 10 countries aimed at understanding the origins, nature and initial outcomes of forest tenure reform. The countries are in Asia (India, Nepal and the Philippines), Africa (Burkina Faso, Cameroon and Ghana) and Latin America (Bolivia, Brazil, Guatemala and Nicaragua). Preliminary research was also conducted in Laos. The project took a rights-based approach and had the simultaneous goals of studying the forest tenure reform and catalysing efforts to advance local control and sustainable forest management The result is a wealth of multi-scalar information and analysis obtained through diverse entities and methods and covering a large variety of reforms in multiple contexts. This CD Rom presents a number of project outputs. It includes 12 country and region reports, 8 policy briefs, 2 Latin America synthesis reports, and several conference papers, journal articles and book chapters. These publications can be accessed by country, and cross-country comparisons are organised by world region. The CD Rom also includes the introductory chapter to Forests for People: Community Rights and Forest Tenure Reform – a book analysing key cross-cutting issues from the research